Risk Factors of Substance abuse among University Students: An Exploratory Study - Gasa, Hlengiwe P.; Mkhize, Sazelo; Shumba, Kemist; Cinini, Samuel F.; Gopal, Nirmala D. (International Journal of Criminology and Sociology, 2022)
Substance abuse is a significant problem among tertiary level students, with alcohol/drug use associated with increased prevalence of negative outcomes, including diminished academic performance, social-interpersonal difficulties, and engaging in risky behaviours. To explore risk factors associated with substance abuse among university students, a qualitative approach was adopted. Twenty on-campus residents were selected through purposive sampling. To elicit their views in-depth interviews were used. Data were thematically analysed, and engendered themes were identified. The findings revealed that various kinds of substances are abused by university students, which include codeine, marijuana (weed), and alcohol. Substance abuse is a kind of behaviour that students either learn or do intentionally, despite their foreknowledge of the negative effects and the risk factors such as peer pressure, stress, and depression. The study concludes that university students are aware of the various negative effects of substance abuse, but they mostly justify it as a way of coping with academic pressure.